(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Shorakhmetov Shoakbar Shorustamovich was born on August 26, 1931, in Chimkent, during a time of great hardship. He lost his father during World War II and grew up in poverty. He had to walk long distances each day to attend school (10-12 km), which shows his early determination and resilience.